NONLINEAR GROWTH MODELS FOR INDIGENOUS VIETNAMESE RI CHICKEN - H. X. Bo; D. V. Hoa; D. T. Nhung; D. T. Hue; D. D. Luc (Journal of Animal and Plant Sciences, 2022)
Chicken growth performance is an important economic trait, so finding the growth curve is essential for the chicken industry including indigenous chicken. Vietnam has many different native chicken breeds and Ri is one of the most famous native chickens. The objective of this study was to find out the best model to estimate the growth of Ri chicken. The body weight of 358 Ri chicken was measured every week until week 20 of age and growth data was analyzed in R using six mathematical functions (Bertalanffy, Bridges, Janoschek, Gompertz, Logistic, and Richards). The results showed that the best models to describe the growth of Ri males and females were Gompertz and Bridges, respectively. The upper asymptotic body weight (α) was estimated for males from 2,130 g (Logistic) to 2,600 g (Bertalanffy), whereas this α value for females was from 1,500 g (Logistic) and 1,816 g (Bertalanffy). Age at the start of the growth acceleration phase was estimated from 2.80 to 3.90 weeks for males and from 2.00 to 3.30 weeks for females. The inflection point for males (7.54 to 9.72 weeks of age) was higher than for females (7.10 to 9.43 weeks of age). Age at the end of the growth deceleration phase was estimated from 16.65 to 24.80 weeks for males and from 12.70 to 25.15 weeks for females. In conclusion, the best model for reporting the Ri chickens’ growth curve was the Gompertz for males and Bridges for females.
Keywords: Body weight; breeding; broilers; growth; modeling